A tragic intersection in Saint Louis, Missouri: Communication, protest, property, and guns. Issue 2 (3rd July 2022) - Rawlins, L. Shelley
ABSTRACT: On June 28, 2020, St. Louis "Expect Us" racial justice protesters marching to their mayor's front door encountered Mark and Patricia McCloskey aiming guns at them as they walked past the couple's mansion on a private road. A clash of "rights" erupted in this situation when viewed through the opposing participants' lenses. On one hand, two persons pulled guns on unarmed protesters that they viewed as encroaching dangerously on their private property. On the other hand, peaceful protesters pursuing their collective cause were forced to detour onto a private street and were met by two persons brandishing guns. This essay examines this troubling encounter in St. Louis when two parties convinced of their starkly different rights protected by law collide. I synthesize Aristotle's and Kenneth Burke's interrelated conceptions of tragedy to analyze these opposing activities in St. Louis by property and gun rights advocates versus the Expect Us political protestors as a tragedy. First, I discuss six historical events in St. Louis from 1906 to 2021 that contextualize this confrontation. Next, I explore the essence of the rights protected by the First and Second Amendments to the Constitution and how they pertain to this encounter. I then define and apply five overlapping features of Aristotle's and Kenneth Burke's accounts of tragedy to consider the implications of this highly publicized event as a microcosm of our presently polarized American society.